Mihael Ambrož in Etbin Henrik Costa - prva ljubljanska demokratična župana - Granda, Stane (Studia Historica Slovenica, 2017)
In this piece the author presents the first two democratic mayors of Ljubljana. Mihael Ambrož (1808- 1864) was mayor of Ljubljana between the years 1861 and 1864. He was distinctly pro-Slovenian, which made it difficult for him to govern. With his personality, appearance and heartiness he was rather unique among Slovenian politicians of the 19. century as well as among the mayors of Ljubljana. He strived for unity among the Slovenian and German inhabitants, but he also wanted to be mayor to all the citizens of Ljubljana first and foremost. As mayor he provided an example that was later politically not continued. Lawyer dr. Etbin Henrik Costa (1832-1875) was mayor between the years 1864 and 1869, and was one of the most contradictory individuals in Slovenian politics. Even his contemporaries did not know whether he should be considered Slovenian or "uskok" - one who switched to the German or at least "Deutschtümler" side when he personally benefited from it.
Keywords: Ambrož, Mihael; Costa, Etbin Henrik; Ljubljana; lokalna samouprava; Slovenija; zgodovina; župani